L’eau à Siğilmāsa (Maroc) : témoins écrits et matériels pour une hydro-histoire du Tāfīlālt (VIIIe-XVe siècles) - Thomas Soubira (Afriques)
Every human society is marked by the daily importance of water for people and animals, housework, agriculture, industry or religion. This management of water necessarily implies strong social interactions. Some written sources show in particular that, in the urban landscape, the major hydraulic works participate to the strategy of political powers that very often enjoy the the benefit of the development and this, in order to establish their legitimacy and attract the inhabitants. Even when the choice of the location of a city depends on a strategic position, the access to water as a basic natural resource for life remains essential and even represents a daily challenge in particular in difficult places such as the oasis areas. Located in the pre-Saharan margins of Morocco today, the ancient city of Sijilmāsa was considered as the hub of trans-Saharan trade between the 8th and 15th century, a city surrounded by the waters in its medieval symbolic representation. Through an analysis of written sources and recent archaeological data, it would be interesting to detect any manifestations of the powers in particular in the material investments given to the urban hydraulic structures, to lay the foundations of a history of water in the oasis of Tāfīlālt.